Development of Android-Based Modern Indonesian Literature Crossword Learning Media Assisted by the Proprofs Application - Hiasa, Fina; Supadi, Supadi; Amrizal, Amrizal; Yanti, Nafri; Agustina, Emi; Adelia, Silvy (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This study aimed to develop and evaluate Android-based crossword puzzle learning media for modern Indonesian literature using the ProProfs application. The research employed a Research and Development (R&D) methodology, collecting data through questionnaires and tests. Three types of questionnaires were distributed: material expert validation, media expert validation, and user validation. Additionally, user tests were conducted to assess comprehension of the literature content transformed into crossword puzzles. The combined validation results from material experts, media experts, and users yielded an overall average score of 3.77 out of 5, indicating that the developed learning media is appropriate for use in educational settings. This finding aligns with the results of four user trials, which demonstrated an average score of 80.6 out of 100, categorized as 'good' performance. These findings suggest that Android-based crossword puzzles can be an effective tool for engaging students with modern Indonesian literature. Future research could explore the long-term impact of this approach on literature comprehension and retention among various student populations.